Health Ailments: What Tourists in India are Prone to and the Remedies.A Study Based on Tourists who Visited Kerala from January to December 2019 (Indian Journal of Public Health Research & Development, 2020)
Background: India is a country in South East Asia with a vast and wide variety of geography and culture.To experience India is something magical. The number of international tourists visiting India have increasedconsiderably in this decade when in comparison with last few decades. Tourism has become one of the majorsources of income for the development of the country. Changes occurred in the world scenario on behalf oftourism have led to the increased concern in health dimension related to it. The risks faced by tourists duringthe visit to tropical destinations like India are very high. Travelers are advised to avoid risks in health bythe WHO which plays a prominent role in sketching out frequent health issues faced by individuals whiletravelling internationally.Objectives: To study the health issues among tourists visiting India. Identify the major causes of thesehealth ailments. To check out the precautions should be adopted by while being in the country inorder toavoid health risks.. And finally to analyze the remedies which can be given to the tourists to avoid theseissues and to make the trip an ever remembering one.Methodology: A survey has been conducted among the tourists who visited India from January 2019 toDecember 2019. The tourists were given questionnaire to get their opinion and experiences regarding health.Results: The basis for the assessment were the responses shown by the participants in the survey .Thesurvey was conducted among 40 international tourists. Among them 10 had not come across any diseaseduring their trip. Diarrhea was reported to 13 people of survey population. Dengue was reported for 5people .Malaria was reported to 4 people and hepatitis for 3. Finally, typhoid for 2 of the participants whoparticipated in the survey.Conclusion:: This assessment gives a detailed description about the health issues encountered by the touristsbecause of their lack of control over food habits. Most of them were affected with diseases due to theirsudden change into spicy food eaters and food tasting from cheap hotels and places which are nearer toslums with polluted water wells.
Keywords: Tourists, Health, Precautions, Remedies.